Nature of the magnetic order and origin of induced ferroelectricity in TbMnO3. - Wilkins, S; Forrest, T; Beale, T; Bland, SR; Walker, H; Mannix, D; Yakhou, F; Prabhakaran, D; Boothroyd, A; Hill, J; Hatton, P; McMorrow, D (2009)
The magnetic structures which endow TbMnO(3) with its multiferroic properties have been reassessed on the basis of a comprehensive soft x-ray resonant scattering (XRS) study. The selectivity of XRS facilitated separation of the various contributions (Mn L(2) edge, Mn 3d moments; Tb M(4) edge, Tb 4f moments), while its variation with azimuth provided information on the moment direction of distinct Fourier components. When the data are combined with a detailed group theory analysis, a new picture emerges of the ferroelectric transition at 28 K. Instead of being driven by the transition from a collinear to a noncollinear magnetic structure, as has previously been supposed, it is shown to occur between two noncollinear structures.